GROWTH PERFORMANCE AND ENZYME ACTIVITIES IN CATFISH (Pangasianodon hypophthalmus) FED WITH WATER HYACINTH-BASED DIET - Dewi Yuniati; Nur Bambang Priyo Utomo; Mia Setiawati; Alimuddin Alimuddin (SEAMEO BIOTROP, 2018)
An alternative substitution of pollard as an imported feed ingredient is a necessity, and one of the potential ingredients is water hyacinth (Eichhornia crassipes). This study was conducted to evaluate growth performance and enzyme activity in catfish (Pangasianodon hypophthalmus). Diet with five different levels of water hyacinth substitute of pollard (0%, 25%, 50%, 75%, and 100%) were fed to catfish for 60 days. Seventy (70) catfish fry with average initial body weight of 2.45 ± 0.15 g were maintained in 100 cm × 80 cm × 60 cm aquaria. Fish fed at satiation level three times daily at 8 am, 12 pm, and 4 pm. With dietary 25% water hyacinth, growth performance and protease activity similar to 0% treatment. Feed intake, protein digestibility, feed efficiency, protein efficiency ratio, and protease and amylase enzyme activities decreased (p<0.05) in those fed with more than 25% water hyacinth. Catfish fed 25% water hyacinth showed significantly (p<0.05) higher daily growth rate, feed efficiency and protein digestibility than those with other treatments. Based on the growth performance and enzyme activity, we can conclude that the optimum dietary level of water hyacinth substitute pollard for fry catfish is 25%.